Does Financial Literacy Moderate the Relationship among Demographic Characteristics and Financial Risk Tolerance? Evidence from Egypt - Amir Ali Shusha (Australasian Accounting, Business and Finance Journal, 2017)
Financial risk tolerance is certainly an important topic for researchers, investors and personal financial planners or consultants. This study purposed to investigate the effect of demographic characteristics on financial risk tolerance among Egyptians. A literature review of demographic determinants of financial risk tolerance showed dialectical results. Therefore, this study attempts to clarify the debatable issues in these results by studying the moderating role of financial literacy in relationships among demographic characteristics and financial risk tolerance. The study sample included 386 respondents representing different segments of Egyptian people. Using the hierarchical regression analysis, the results demonstrated that there were significant effects of gender, age, educational level and annual income on financial risk tolerance. Moreover, the financial literacy moderates the relationships among demographic characteristics of individuals and their tendency to take a risk.
Keywords: financial risk tolerance; financial literacy; demographic characteristics; moderated role personal finance; Egypt.